Transfer of Pt marker nanoparticles in a three-link trophic chain chlorella Beijer-Daphnia magna Straus-Cyprinus carpio - Morgalev, Yuri N. (Nanobiotechnology reports)
The entrance of Pt marker nanoparticles (NPs) into the hydrosphere leads to association with unicellular algae Chlorella (the bioaccumulation factor reaches 10 000). There is a significant elimination time (t(1/2) = 7 days) even with single contamination of the hydrosphere. Pt NPs, entering the hydrosphere, accumulate in the organism Daphnia magna Straus in large numbers (bioaccumulation factor of 1000-2000), starting from the first day, which can be dangerous for consumers of a higher trophic level. The accumulation of NPs occurs both in the digestive tract and on the surface of the body (t(1/2) = 3 h). The accumulation of NPs during transmission through the food chain with chlorella contaminated with nanoparticles exceeds accumulation from the environment by 4 times, which is associated with the preliminary accumulation of NPs by food (chlorella) and absorption by Daphnia of NPs in a concentrated form. NPs accumulate in fish from the environment (bioaccumulation factor of up to 2500) and along the food chain (bioaccumulation factor of up to 350). Purification from NPs during accumulation along the food chain occurs much more slowly than in the series with the accumulation of NPs from the environment. When using fish products contaminated with NPs, such organs and tissues as skin, muscles and skeleton are of greatest risk.